THE ANALYSIS OF EROSION AND SEDIMENT DELIVERY RATIO IN PADANG GUCI OF KAUR REGENCY - Ahadi Somad Syahlan; Khairul Amri; M. Faiz Barchia (Universitas Bengkulu, 2019)
This research about analysis of erosion and land critical level on watershed (DAS) Padang Guci of Kaur Regency is based on few watershed in Bengkulu Province that allegedly has decreased function, which on of it is watershed (DAS) Padang Guci. Watershed (DAS) is an ecosystem which main elements consist of natural resources, water, and vegetation, and also human resources as its user. Several performance indicators of watershed (DAS) that can bemeasured is the index of land cover, forest land cover condition, erosion hazard index, and land management index. Watershed (DAS) Padang Guci has land area about 52689,2 ha. This research using data analysis and maps with Geographic Information System (GIS) in order to get the result of studies that determine the performance of its watershed. The result of the analysis using Geographic Information System (GIS) in the watershed (DAS) Padang Guci is60% of the total area, erosion occur with a very light level. Critical Potential land dominates the cultivation area is 65,41%, while 59,73% critical potential dominates the protected area outside the protected forest. Sediment delivery ratio that obtained was 0,024. The decrease of region function well in cultivation area. It conclude that for the performance of the watershed (DAS) Padang Guci based on land use indicators overall categorized still safe. Keywords : Watershed (DAS), Critical Level’s Area, Erosion, GIS